2014
DOI: 10.1371/journal.pone.0097603
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Chronic Fluoxetine Treatment on Neurogenesis and Tryptophan Hydroxylase Expression in Adolescent and Adult Rats

Abstract: The antidepressant drug fluoxetine (Prozac) has been increasingly prescribed to children and adolescents with depressive disorders despite a lack of thorough understanding of its therapeutic effects in the paediatric population and of its putative neurodevelopmental effects. Within the framework of PRIOMEDCHILD ERA-NET, we investigated; a) effects of chronic fluoxetine treatment on adult hippocampal neurogenesis, a structural readout relevant for antidepressant action and hippocampal development; b) effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 70 publications
6
34
0
1
Order By: Relevance
“…(Kempermann et al, 2006;Veenema et al, 2007b;Pawluski et al, 2009;Barha et al, 2011). While the numbers we found here were largely in line with studies on rats of related ages (Oomen et al, , 2011Klomp et al, 2014), MD did not affect neurogenesis in female rats 17 weeks of age, indicating that the decreased neurogenesis found earlier in MD females at PND 21 (Oomen et al, 2009) does not last into later ages. The same applies to the earlier found decrease in DG cell number and density measured at 10 weeks after MD at PND3 (Oomen et al, 2011), which was not maintained in the animals we collected around 17 weeks of age.…”
Section: Discussionsupporting
confidence: 90%
“…(Kempermann et al, 2006;Veenema et al, 2007b;Pawluski et al, 2009;Barha et al, 2011). While the numbers we found here were largely in line with studies on rats of related ages (Oomen et al, , 2011Klomp et al, 2014), MD did not affect neurogenesis in female rats 17 weeks of age, indicating that the decreased neurogenesis found earlier in MD females at PND 21 (Oomen et al, 2009) does not last into later ages. The same applies to the earlier found decrease in DG cell number and density measured at 10 weeks after MD at PND3 (Oomen et al, 2011), which was not maintained in the animals we collected around 17 weeks of age.…”
Section: Discussionsupporting
confidence: 90%
“…7, 42 However, recent data suggest that FLX may not be effective in enhancing neurogenesis 16, 17 or even reduce it. 16, 17, 18, 19, 43, 44 Similar contradictory results have been found for the effects of SSRI on hippocampal volumetric reduction, which is considered a further feature of depression. 45 Overall, we found that FLX has no effect on neurogenesis in the enriched condition, but leads to detrimental consequences on proliferation in the stressful condition (Figure 2a and b).…”
Section: Resultsmentioning
confidence: 55%
“…For instance, many studies show that SSRI administration reduces depression-like behavior, 5, 6 enhances neurogenesis, 7 increases brain-derived neurotrophic factor (BDNF) levels, 5, 8 reduces hypothalamic–pituitary–adrenal (HPA) axis activity 9, 10 and heightens long-term potentiation (LTP). 11 However, many others reported no or opposite effects concerning the same endpoints: behavior, 12, 13, 14, 15 neurogenesis, 16, 17, 18, 19, 20 BDNF levels, 21, 22, 23, 24, 25, 26 HPA axis activity 27, 28 and LTP. 29, 30 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, paroxetine and other SSRIs have proven neuroprotective in several animal models of neurodegenerative diseases (Chiou et al , 2006; Chung et al , 2010; Chung et al , 2011; Lim et al , 2009; Mattson et al , 2004; Nelson et al , 2007; Peng et al , 2008; Shibui et al , 2009). SSRI neuroprotection has been attributed to inhibition of neuroinflammation and oxidative stress (Chiou et al , 2006; Chung et al , 2010; Chung et al , 2011; Lim et al , 2009; Zhang et al , 2012), inhibition of apoptosis and promotion of neuroprotective BDNF signaling (Mattson et al , 2004), rescue or enhancement of neurogenesis (Jiang et al , 2014; Klomp et al , 2014; Lee et al , 2011; Stagni et al , 2013), and even inhibition of glutamate excitotoxicity (Vizi et al , 2013) in both animal models and cell culture, all of which have been implicated in the development of HAND (Lindl et al , 2010; Mocchetti et al , 2014; Potter et al , 2013; Steiner et al , 2006). In this study, we found FluPar treatment prevented neurodegeneration without significantly inhibiting multiple measures of neuroinflammation, indicating further investigation into the mechanism of action is needed.…”
Section: Discussionmentioning
confidence: 99%